Renal Nerve Activity and Arterial Depressor Responses Induced by Neuromodulation of the Deep Peroneal Nerve in Spontaneously Hypertensive Rats - Gonzalez-Gonzalez, Maria Alejandra; Romero, Kevin; Beitter, John; Lloyd, David; Lam, Danny V.; Hernandez-Reynoso, Ana Guadalupe; Kanneganti, Aswini; Kim, Han-Kyul; Bjune, Caroline K.; Smith, Scott; Vongpatanasin, Wanpen; Romero-Ortega, Mario I. (Frontiers in Neuroscience, 2022)
Hypertension is a main cause of death in the US with more than 103 million adults affected. While pharmacological treatments are effective, blood pressure (BP) remains uncontrolled in 50-60% of resistant hypertensive subjects. Using a custom wired miniature electrode, we previously reported that deep peroneal nerve stimulation (DPNS) elicited acute cardiovascular depressor responses in anesthetized spontaneously hypertensive rats (SHR). Here we further study this effect by implementing a wireless system, and exploring different stimulation parameters to achieve a maximum depressor response. Our results indicate that DPNS consistently induces a reduction in blood pressure, and suggest that renal sympathetic nerve activity (RSNA) is altered by this bioelectronic treatment. To test the acute effect of DPNS in awake animals we developed a novel miniaturized wireless microchannel electrode (w-CE), with a Z-shaped microchannel through which the target nerves slide and lock into the recording/stimulation chamber. Animals implanted with w-CE and BP telemetry systems for 3 weeks showed average BP of 150 +/- 14 mmHg, which reduced significantly by an active DPNS session to 135 +/- 8 mmHg (p< 0.04), but not in sham-treated animals. The depressor response in animals with an active w-CE progressively returned to baseline levels 14 min later (164 +/- 26 mmHg). This depressor response was confirmed in restrained fully awake animals that received DPNS for 10 days, where tail cuff BP measurements showed that systolic BP in SHR lowered 10% at 1 hr and 16 % 2 hr after the DPNS compared to the post-implantation baseline. Together, these results support the use of DPN neuromodulation as a possible strategy to lower BP in drug-resistant hypertension.